2009
DOI: 10.2193/2008-326
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry‐Flavored Baits for Pharmaceutical Delivery to Feral Swine

Abstract: More effective methods to control feral swine (Sus scrofa) damage are needed. We evaluated 8 oral delivery systems designed to deliver pharmaceuticals to feral swine on 2 properties in southern Texas, USA. We used modified PIGOUT® feral pig bait (Animal Control Technologies Australia P/L, Somerton, Victoria, Australia) throughout our trials to compare species‐specific visitation and removal rates. Given our consistent finding of high nontarget removal of baits intended for feral swine, we question whether a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Two non-target species, raccoons and collared peccary, were documented not visiting sites with strawberry scent; however, apple scent appeared to attract raccoons (Campbell and Long 2008). Strawberry flavoring has also provided reliable attraction to wild pigs without drawing raccoons; however, deer were attracted to strawberry flavoring (Campbell and Long 2009). …”
Section: Non-target Species Impactsmentioning
confidence: 99%
“…Two non-target species, raccoons and collared peccary, were documented not visiting sites with strawberry scent; however, apple scent appeared to attract raccoons (Campbell and Long 2008). Strawberry flavoring has also provided reliable attraction to wild pigs without drawing raccoons; however, deer were attracted to strawberry flavoring (Campbell and Long 2009). …”
Section: Non-target Species Impactsmentioning
confidence: 99%
“…Though researchers observed bait removal by a diverse suite of species including cattle, white-tailed deer, and eastern cottontail rabbits (Sylvilagus floridanus), fish-flavored baits that were distributed in a cluster were removed by feral swine at a rate greater than expected (Campbell and Long 2007). The third trial compared fish-flavored baits, vegetable-flavored baits, vegetable-flavored baits with a strawberry-flavored feed additive, fish-flavored baits with synthetic fermented egg attractant/repellent, and vegetable flavored baits with synthetic fermented egg attractant/repellent (Campbell and Long 2009b). The strawberry-flavored feed additive was previously identified as a candidate feral swine attractant (Campbell and Long 2008).…”
Section: Feral Swine Oral Delivery Systems Research In the Usmentioning
confidence: 99%
“…The strawberry-flavored feed additive was previously identified as a candidate feral swine attractant (Campbell and Long 2008). Again, investigators found that many species removed PIGOUT ® baits and that the addition of a strawberry-flavored feed additive and synthetic fermented egg attractant/repellent did not universally improve the feral swine-specific attributes of the delivery system (Campbell and Long 2009b). The fourth trial compared fish-flavored PIGOUT ® , vegetableflavored PIGOUT ® , and vegetable-flavored PIGOUT ® with a strawberry-flavored feed additive that were surfacedeployed and buried to a depth of 10 cm (Campbell and Long 2009b).…”
Section: Feral Swine Oral Delivery Systems Research In the Usmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of products have been used to increase the attractiveness of baits for wild mammals; strawberry (cotton wool impregnated with a strawberry flavouring) has been used successfully as an attractant for feral swine (Campbell and Long 2009), cinnamon-truffle powder (as a bait additive) for feral swine piglets (Ballesteros et al 2009), apple (both apple juice and apple odour) for white-tailed deer (Bean and Mason 1995), marshmallow (as a bait flavouring) for gray foxes (Steelman et al 2000) and cinnamon oil and anise oil (as bait additives) for brushtail possums (Morgan 1990;Aldwell et al 2003a). Fish products have worked well as attractants for raccoons , skunks (Jojola et al 2007), mongooses (Creekmore et al 1994) and red foxes (Smith and Woods 2007), whereas offal has proved a useful attractant for dogs (Estrada et al 2001) and coyotes (Stolzenburg and Howard 1989).…”
Section: Introductionmentioning
confidence: 99%